Anxiolytic Effects of Flavonoids in Animal Models of Posttraumatic Stress Disorder. (13th December 2012) - Zhang, Li-Ming; Yao, Jia-Zhi; Li, Yang; Li, Kai; Chen, Hong-Xia; Zhang, You-Zhi; Li, Yun-Feng
Abstract : The dysregulation of the serotonergic system has long been recognized as an important factor underlying the pathophysiology of PTSD. To date, SSRIs have already been established as the firstline pharmacotherapeutic agents for treating acute and chronic PTSD. However, SSRIs largely have several disadvantages which limit their utility. Our previous study has also shown that administration of the total flavonoids, isolated from the extract of Xiaobuxin-Tang (XBXT, mild mind-easing decoction), comprising four Chinese medicines including Haematitum, Flos Inulae, Folium Phyllostachydis Henonis, and Semen Sojae Preparatum, exerted significant antidepressant-like effect in chronically mildly stressed rats, possibly mediated by serotonergic activation. Since the central serotonergic dysfunction is an important and well-known cause mediating the pathophysiology of trauma-related symptoms in PTSD, it is reasonable to predict that flavonoids may exert therapeutic effects on PTSD in animal models. Therefore, the present study aims to examine the effect of flavonoids in alleviating the enhanced anxiety and fear response induced in two PTSD animal models. Ser, an SSRI, was administered as a positive control. Furthermore, the changes of brain monoaminergic neurotransmitters after chronic flavonoids administration have also been assessed in SPS-treated rats.